Test Cross Evaluation of Upland Cotton Accessions for Selected Fiber Properties. Issue 1 (1st January 2014) - Beyer, Benjamin M.; Smith, C. Wayne; Percy, Richard; Hague, Steve; Hequet, Eric F.
ABSTRACT: Texas A&M AgriLife Research released several upland cotton ( Gossypium hirsutum L.) germplasm lines that exhibit near extra long and extra long staple (ELS) upper half mean length (UHML) fibers, similar to those produced by pima cotton ( Gossypium barbadense L.) and significantly longer than those of upland cultivars currently grown in the United States. While present‐day global marketing systems do not reward the production of such upland cotton fibers, future competitiveness of upland cotton may depend on availability of such variability. Thirty‐six improved upland cotton cultivar accessions from the USDA‐ARS Cotton Collection were crossed to two testers to determine if any contained alleles for additional improvement in fiber length or strength parameters of germplasm developed by Texas A&M AgriLife Research. 'Tamcot CAMD‐E' was chosen as a standard fiber quality tester and TAM B182‐33 ELS was the elite fiber quality tester. The lines, testers, and F1 s were grown in Tecoman, Colima, Mexico, and at College Station, TX, in 2010 and at College Station only in 2011. Fiber data were subjected to line × tester analysis. Funtua FT‐5 from northern Africa and Stoneville 474 from the United States may harbor additional UHML and length uniformity alleles for improving TAM B182‐33 ELS. Phytogen 72 (United States) and BJA 592 (northern Africa) may contain additional alleles to improve fiber bundle strength.